Association between interleukin-35 polymorphisms and coronary heart disease in the Chinese Zhuang population: a case–control study. Issue 5 (August 2018) - Lin, Yingzhong; Xue, Yan; Huang, Xinshun; Lu, Jianyong; Yang, Zicong; Ye, Jing; Zhang, Shu; Liu, Ling; Liu, Yu; Shi, Ying
Abstract : Objectives: Inflammatory cytokines play an important role in the pathogenesis of cardiovascular disease. Few studies have investigated the association between interleukin-35 ( IL-35 ) genetic variants and the risk of coronary heart disease (CHD). We examined the association between IL-35 polymorphisms and CHD in the Chinese Zhuang population. Patients and methods: A total of 707 CHD patients and 707 age-matched and sex-matched controls were enrolled in this case–control study. Genotypes of the single nucleotide polymorphisms (SNPs) of IL-35, including rs428253, rs6613, rs9807813, rs2243115, rs568408, rs582054, rs583911, rs4740, and rs393581, were examined by MassArray. Plasma IL-35 level was measured using an enzyme-linked immunosorbent assay. The multivariate logistic regression model was used to evaluate the association between the SNPs and the risk of CHD. Results: In the Chinese Zhuang population, compared with the GG genotype of EBI3 rs428253, individuals with the CC genotype had a 2.02-fold (95% confidence interval: 1.07–3.84, P =0.031) higher risk of CHD. Further adjustment for potential risk factors did not alter the positive association (CC vs. GG, odds ratio=2.30, 95% confidence interval: 1.16–4.54, P =0.042). SNPs rs4740, rs2243115, rs568408, and rs582054 were not statistically related to the risk of CHD. The plasma IL-35 levels showed a marginally significant difference between rs428253 genotypes [GG: 13.39 (7.89–19.25) vs. CC+GC: 17.53 (8.98–22.56) pg/ml, P =0.057]. Conclusion: The EBI3 rs428253 CC genotype was associated with an increased risk of CHD in the Chinese Zhuang population, although no significant difference in IL-35 levels was observed between genotypes in healthy controls. Abstract : Supplemental Digital Content is available in the text.